The Empowering Comparative Supply Chain Operations of Batik SMEs through Uniqueness of Packaging, Productivity and Innovation - Yana Hendayana; Suryana Suryana; M.S Disman; H. Mulyadi; Jumadil Saputra (International Journal of Supply Chain Management, 2019)
The objective of this study is to analyse the impact uniqueness of packaging, productivity and innovation to empowering competitiveness Batik SMEs in West Java Indonesia based on the supply chain operation. In Indonesia the packaging design of batik cloth strengthens its character. The brand image that mostly SMEs in Indonesia want to highlight from batik packaging is the traditional yet elegant impression. The traditional impression was chosen because it wanted to highlight the side of batik craft as a distinctive souvenir and culture, while the elegant image was chosen because so far people thought that the craft was mostly only cheap, especially just packaged using clear plastic or no packaging which became less attractive if given to someone else as a souvenir. With unique packaging, the public image of batik handicraft products expected to be higher. In order to strengthen competitiveness and raise productivity in SMEs Batik in West Java Indonesia, the design was made with an innovated elegant concept so that the image of batik products became higher. Unique and attractive packaging can be seen from the encyclopaedia layout that has never existed for batik packaging and also because so far batik products rarely have packaging. That's why this packaging design is in accordance with the goals and functions to be achieved. For data testing in this research used Partial Least Square (PLS), explanatory method, and simple random sampling. The results shown that the uniqueness of packaging and innovation raise productivity and impact the competitiveness of Batik SMEs in West Java as much as.